Drop Dissolution Intensified by Acoustic Levitation - Jan-Paul Ruiken; Jörn Villwock; Matthias Kraume (Micromachines, 2024)
Acoustic levitation can provide significant benefits for many fundamental research questions. However, it is important to consider that the acoustic field influences the measurement environment. This work focuses on the dissolution of immobilised drops using acoustic levitation in liquid–liquid systems. Previous work demonstrated that the acoustic field of standing waves impacts mass transfer by affecting the spread of dissolved substances in the continuous phase in two distinct ways: (I) solutes may either pass through nodal planes of the standing waves or (II) not pass. The binary systems examined for case (I) are 1-hexanol–water and 1-butanol–water, and for case (II), n-butyl acetate–water and toluene–water. This work quantifies the intensification effect of acoustic levitation on dissolution for the two types of behaviour, by comparing them with reference measurements of mechanically attached dissolving drops. The system was designed to ensure minimal intensification. The minimum intensification of mass transfer for levitating drops in the used setup of case (I) was 25%, and for case (II), it was 65%, both increasing with decreasing surface-equivalent diameter. With this understanding, acoustic levitation can be used more accurately in the field of mass transfer studies.